Mouse hunt - Riche, Alan; Cohen, bruce; Ludwig, Tony; Verbinski, Gore; Dreamworks Pictures (Universal City, CA : Dreamworks Home Entertainment, 1998)
Down-on-their luck brothers Lars and Ernie Smuntz don't think much of the crumbling old mansion they inherit until they discover that their dilapidated estate is actually worth millions. But before they can cash in, they've got to rid the house of its single, stubborn occupant: a tiny and tenacious mouse. What might seem like child's play becomes an epic battle of hysterical proportions
Title from title screen
Subtitles in English and Mandarin
Screenplay by Adam Rifkin ; director of photography, Phedon Papamichael; production designer, Linda DeScenna; editor, Craig Wood; music, Alan Silvestri
Casts: Nathan Lane, Lee Evans, Vicki Lewis, Maury Chaykin, Eric Christmas
Keywords: Mice -- Drama; Brothers -- Drama; Comedy films